Studies on Floral Biology of Seven Litchi (Litchi chinensis Sonn.) Cultivars - P K Pathak (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2013)
Floral biology of seven litchi cultivars (China, Deshi, Elaichi, Kasba, McLean, Nafarpal and Piazi) was studied. Cultivar Deshi showed panicle formation on 2nd January, while panicle initiation was early (10th February) in cv. Piazi. Flowering duration varied between 13±4 days in 'China' and 30±3 days in 'Piazi'. Male:hermaphrodite flower ratio was maximum in 'Piazi' (5.8:1) and minimum in 'China' (2.74:1). In general, anthesis was maximum between 7 and 8 AM, while, anther dehiscence was maximum between 9 and 10 AM. Percentage of viable pollen varied between 82.14% in cv. Elaichi and 91.38% in cv. Piazi Pollen germination was higher in 15% sucrose solution.